2017
DOI: 10.1177/2325967117730805
|View full text |Cite
|
Sign up to set email alerts
|

The Anterolateral Complex of the Knee

Abstract: Background:Significant controversy exists regarding the anterolateral structures of the knee.Purpose:To determine the layer-by-layer anatomic structure of the anterolateral complex of the knee.Study Design:Descriptive laboratory study.Methods:Twenty fresh-frozen cadaveric knees (age range, 38-56 years) underwent a layer-by-layer dissection to systematically expose and identify the various structures of the anterolateral complex. Quantitative measurements were performed, and each layer was documented with high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 48 publications
1
62
0
4
Order By: Relevance
“…The clinical outcomes after combined ACL and ALL reconstruction are promising despite the ongoing debate about the biomechanical characteristics of the ALL. 20,21 Zaffagnini et al reported better control of static knee laxity, reduced mediolateral instability in early flexion, and reduced rotatory instability at 90°of flexion in patients operated using a single-bundle ACL reconstruction with extraarticular augmentation compared with double-bundle ACL reconstruction. 22 In this study, we observed that 80% of the patients had normal or nearly normal knees using IKDC rating system after at least 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcomes after combined ACL and ALL reconstruction are promising despite the ongoing debate about the biomechanical characteristics of the ALL. 20,21 Zaffagnini et al reported better control of static knee laxity, reduced mediolateral instability in early flexion, and reduced rotatory instability at 90°of flexion in patients operated using a single-bundle ACL reconstruction with extraarticular augmentation compared with double-bundle ACL reconstruction. 22 In this study, we observed that 80% of the patients had normal or nearly normal knees using IKDC rating system after at least 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately for orthopaedics, members of the University of Pittsburgh Orthopedic Department have provided this type of zeal and have advanced the concept of the anterolateral complex of the knee. [6][7][8][9] Their work would generally not support the concept that the ALL is a separate structure worthy of the term "ligament." Regrettably, much of their work on the subject was not reviewed because de Lima et al 1 limited their searches to "anterolateral ligament."…”
Section: See Related Article On Page 670mentioning
confidence: 92%
“…Possibly because of the complex anatomy of this region, new studies are still being published with new information with regard to these structures, and yet the results are often conflicting, mainly with regard to the presence or absence of a true ligamentous structure within the anterolateral capsule, and the anatomic parameters of the capsulous-osseous layer. 9 , 14 The studies of Herbst et al 14 and Godin et al 9 are examples of meticulous well-performed dissections that present innumerable similarities but some points of difference. Godin et al, 9 for example, described the capsulous-osseous layer as “attached just proximal to the lateral gastrocnemius tubercle on the distal ridge 19.1 mm proximal to the lateral epicondyle, with an attachment area of 48.9 mm 2 ,” and Herbst et al described it as a layer contiguous with the fascia of the lateral gastrocnemius and plantaris muscles, with only flimsy fibers variably inserted in the area of the lateral femoral epicondyle.…”
Section: Anatomymentioning
confidence: 99%